Electronic cigarette: A review - Vinay Mahishale (Archives of Medicine and Health Sciences, 2014)
The principal addictive component of tobacco smoke is nicotine. The mechanisms of nicotine addiction are highly complex and are responsible for maintenance of smoking behaviour. Use of electronic cigarettes (E-cigarettes), devices that deliver a nicotine containing vapor has increased rapidly across the world. They are marketed as a "healthier alternatives" to conventional cigarettes. There is extensive debate over long-term safety and efficacy of these devices on public health. Studies show that the vapor generated from the E-cigarettes has a variable amount of nicotine and potential harmful toxins. Until robust research demonstrates the safety of E-cigarettes and efficacy in the treatment of tobacco dependence, their role as safe smoking cessation tool is unclear. This review highlights the recent data regarding E-cigarettes toxicity, impact on lung function, and efficacy in smoking reduction and cessation.